Apakah Faktor Internal Masih Relevan Dalam Menentukan Jurusan Kuliah? - Saragih, Fernando; Simbolon, Gallex (Universitas Nusa Cendana, 2022)
Decision-making is an essential thing in determining the direction of a program. One form of decision-making is choosing college majors. Internal and external factors strongly influence this determination, but interest and motivation to learn in a student. Where this study aims to see the influence of interest and motivation to learn in making decisions to choose majors, this research is a quantitative type with an ex post facto model using primary data (the variables x1, x2, and x3 consist of 10, 13 and 15 statements). Determination of this research using the incidental method through the distribution of online questionnaires. The analysis used in this process is multiple regression with the help of the SPSS 23 application; where before the regression is carried out, the researcher must pay attention to the instrument test and classical assumptions. Based on the results of the analysis that has been carried out, it can be concluded that there is a positive and significant influence between interest (variable x1 of 0.353) and motivation (variable of x1 of 0.282) on the decision to choose majors.